PERNIKAHAN DINI PERSPEKTIF HUKUM ISLAM DAN HUKUM POSITIF DI INDONESIA - Achmad Al-Muhajir; Amrotus Soviah (Sekolah Tinggi Ilmu Syariah Abu Zairi Bondowoso, 2023)
This research aim to know, view punish Islam and related positive law of nuptials phenomenon early. This research type that is research qualitative and use descriptive approach. As for source of used data that is primary data and data of sekunder. Technique data collecting cover: Observation, Interview and Documentation. Obtained data from result of research processed by using data analysis descriptively qualitative. Result of this research indicate that (i) Conception nuptials of age early according to Islam is immeasurable, its nucleus; core, nuptials early as long as fufilled its foundation condition of validity according to fiqh. (ii) According to Positive Law, pursuant to newest Law that is [Code/Law] Number 16 Year 2019 about Change of Law Number 1 Year 1974 is connubial of marriage age definition have been turned into 19 year between men age and also woman. (iii) Resistance and constraint in face of nuptials phenomenon is early evaluated from existing invitation aspect that order legislation of marriage only made by complement value after books concept of fiqh traditional. This is one of the cause less maximal it application Legislation Of contemporary Law Family Moslem in field because of by legislation content there are some which interfere in or minimize disagree with philosophic value, and yuridis of sosiologis going into effect in society majority. As for effort conducted for the meminimalisir of nuptials early that is; grow awareness at society for the importance of education at children exself and the rising generation, cultivation of education of religion for every child, and also is same activity of party with KUA District